Sustainability in engineering design an undergraduate text - Johnson, Anthony; Gibson, Andy (Academic Press, 2014)
Annotation
Includes bibliographical references and index. - Print version record; title from PDF title page (viewed September 14, 2022)
Keywords: Engineering design -- Textbooks; Sustainable engineering -- Textbooks; TECHNOLOGY & ENGINEERING; Engineering (General); TECHNOLOGY & ENGINEERING; Reference; Engineering design; Sustainable engineering; Textbooks